Cryopreservation of sessile oak (Quercus petraea (Matt.) Liebl.) plumules using aluminium cryo-plates: influence of cryoprotection and drying - Wasileńczyk, Urszula; Wawrzyniak, Mikołaj Krzysztof; Martins, João Paulo Rodrigues; Kosek, Paulina; Chmielarz, Paweł (Plant methods, 2024)
BACKGROUND QUERCUS: seeds that are recalcitrant to desiccation and freezing temperatures cannot be stored in gene banks under conventional conditions. However, the germplasm of some recalcitrant seeded species can be stored in liquid nitrogen (-196 °C). Unfortunately, for many species, among them for almost the whole genus Quercus, an effective cryostorage method is still unknown. In this study, we propose a successful cryostorage protocol for Quercus petraea (Matt.) Liebl. germplasm using plumules (a shoot apical meristem of an embryo) frozen on aluminium cryo-plates. RESULTS: The plumules isolated from the acorns of ten provenances were prestored in 0.5 M sucrose solution (for 18 h). To form alginate beads (one plumule per bead), the plumules were placed in the wells of a cryo-plate and embedded in calcium alginate gel. For cryoprotection, the encapsulated plumules were immersed in cryoprotectant solution containing 2.0 M glycerol and different concentrations of sucrose (0.8-1.2 M) for 40 min at 25 °C and desiccated under a laminar flow cabinet for 1.0-4.0 h. Cryo-plates with plumules were directly immersed in liquid nitrogen and then cryostored for 30 min. For rewarming, cryo-plates with plumules were immersed in 1.0 M sucrose solution and rehydrated for 15 min at 25 °C. Survival rates varied from 25.8 to 83.4 were achieved after cryoprotection in 1.0 M sucrose solution and the drying of plumules for 2 h. The in vitro regrowth rate of cryopreserved plumules varied among provenances and was 26-77%. CONCLUSIONS: This study presents, for the first time, a successful, simple and effective protocol for the cryopreservation of Q. petraea germplasm that could be used in gene banks. The experiment was successfully repeated on seeds from various provenances, each yielding similar, good results. However, seed quality and storage time after harvesting are important factors in plumule regrowth after cryopreservation.